A molecular adsorbent recycling system in treating posthepatectomy acute hepatic failure patients with hepatocellular carcinoma: a bridge to liver transplantation - Wang, Yu; Liu, Yihe; Zheng, Weiping; Ming, Yu; Shen, Zhongyang (Chinese journal of clinical oncology, 2006)
R73; OBJECTIVE To evaluate the effect and safety of a Molecular Adsorbent Recycling System (MARS) in treating posthepatoectomy hepatic failure (AHF) patients surgically treated for primary hepatocellular carcinoma (HCC).METHODS 12 AHF patients induced by resection of HCC were treated with MARS before orthotopic liver transplantation (OLT). Their vital signs, urine volume, APACHE Ⅲ and Glasgow scores were monitored. Routine laboratory blood tests, measurements of coagulatory function, liver and kidney function, serum ammonia, lactic acid and blood gas were conducted before and after treatment with MARS. All of the patients were followed up for a period of 6 months after OLT for prognosis and complication assessment.RESULTS Each patient was treated with MARS for 2～5 times (average of 3.6) with a length of 8～24 h each time. Their mean arterial blood pressure and urine volume were improved, APACHE Ⅲ and Glasgow scores were better. Liver function was improved with the following alterations before and after treatment with MARS: serum ammonia (127.1±21.4 umol/L vs. 77.4±19.7 umol/L, P＜0.05), lactic acid (6.53±0.45 mmol/L vs. 3.75± 0.40 mmol/L, P＜0.05) and total bilirubin (452.3±153.7 umol/L vs. 230.9± 115.2 umol/L, P＜0.05). However, there was no significant change in platelet count (44.25±3.60×109/L vs. 43.19±8.26×109/L, P＞0.05) on international normalized ratio (INR) (2.74±0.50 vs. 2.82±0.60, P＞0.05), which showed the safety of MARS. For all patients no serious adverse effects occurred during the treatment with MARS.CONCLUSION MARS is effective and safe for treatment of AHF patients with HCC, especially as a bridge to OLT when a donor organ is not available.